Pitfalls in Collecting Blood Specimens for Antibiotic Assay - Sirinavin, Sayomporn (1979)
Obtaining blood samples for antibiotic analysis from intravenous lines through which the antibiotic had been administered was critically evaluated. Flushing volumes required to remove contaminating antibiotic varied with the type of antibiotic and with different plastics. Obtaining blood specimens from the intravenous lines is not practical in infants and not advised in adults.